A Study on the Improvement of Forest Fire Extinguishing Systems: Focusing on Aerial Firefighting Resources - Jin-Young Kim; Myeong-Ju Kim; 이의재; 채희문; 이상덕 (Journal of Forest and Environmental Science, 2025)
The frequency and scale of forest fires are increasing worldwide due to climate change, land use changes, and extreme weather events. South Korea has experienced repeated large-scale forest fires, particularly in mountainous regions such as the Yeongdong area of Gangwon Province and northern North Gyeongsang Province, causing significant social, economic, and environmental damage. In rugged terrain, aerial firefighting resources including helicopters and fixed-wing aircraft are crucial for early response and suppression. However, operations face challenges such as fragmented command structures, inefficient resource allocation, and aging equipment. This study analyzed the operational status of aerial suppression resources in South Korea from 1994 to 2023 using long term forest fire occurrence and deployment data. Results show a seasonal concentration of fires in spring, clustering in high-risk areas, and a positive correlation between burned area, suppression time, and aerial resource deployments. However, simply increasing resource numbers does not necessarily reduce damage without systemic improvements. To improve effectiveness, the study proposes: (1) establishing an integrated national command system and real-time information sharing platform; (2) implementing risk-based pre-deployment strategies by region and season; (3) prioritizing large helicopters for high-risk zones; and (4) enabling flexible seasonal deployment of medium-class aircraft. Further measures include replacing aging equipment, standardizing maintenance cycles, securing multifunctional suppression resources, and expanding training to address the aging pilot workforce. From a policy perspective, developing a mid to long term national roadmap, enhancing cooperation between central and local governments, and expanding publicly owned aerial resources are essential. Reducing reliance on short term private contracts and ensuring year round optimal allocation will strengthen South Korea’s resilience to future large-scale forest fires. These integrated strategies can enable faster, more efficient, and more coordinated suppression efforts, ultimately mitigating the impacts of catastrophic events.